Terahertz Electromagnetically Induced Transparency with Electric-Field-Coupled Inductor-Capacitor Resonators on LCP Substrate - Haotian Ling; Zhaolin Li; Ke Li; Ruiqi Zhao; Pengfei Ma; Yongping Zhou; Jingxuan Li; Xiaoyu Xu; Yevhen Yashchyshyn; Xudong Zou; Yifei Zhang (Crystals, 2023)
Electromagnetically induced transparency (EIT) metamaterials (MTMs) based on the bright-dark mode theory have gained great interest in slow light, sensing, and energy storage in recent years. Typically, various split ring resonators with magnetic response have been proposed as dark resonators in EIT MTMs. Here, we have employed a cut-wire (CW) and two electric-field-coupled inductor-capacitor (ELC) resonators with a pure electrical response on a liquid crystal polymer (LCP) substrate with a low loss tangent to fulfill the EIT effect in the terahertz (THz) region. The former works as the bright mode, and the latter functions as the dark mode. The EIT phenomenon results from the destructive interference between these two modes, which can be verified by numerical simulation and near field distribution. In addition, a Lorentz oscillator model was studied to quantitatively analyze the relationship between the coupling strength and the coupling distance. As a demonstration, an EIT MTM device with 5000 units was fabricated and characterized, which showed a transmission window with a peak value of 0.75 at 0.414 THz. This work may inspire new multifunctional EIT MTMs, especially the flexible applications at THz frequencies.